Mushroom tyrosinase enzyme catalysis: synthesis of larvicidal active geranylacetone derivatives against Culex quinquesfasciatus and molecular docking studies - Mullaivendhan, Janani; Ahamed, Anis; Arif, Ibrahim A.; Raman, Gurusamy; Akbar, Idhayadhulla (Frontiers in Chemistry, 2024)
The grindstone process, which uses tyrosinase as a catalyst, was used to create analogues of geranylacetone. Tyrosinase was used to prepare the Mannich base under favourable reaction conditions, resulting in a high yield. All synthesized compounds were characterized using FTIR, Nuclear magnetic resonance, and mass spectral analyses. The active geranylacetone derivatives (1a-l) were investigated for larvicidal activity against Culex quinquefasciatus; compound 1b (LD50:20.7 µg/mL) was noticeably more effective than geranylacetone (LD50: >100 µg/mL) and permethrin (LD50: 24.4 µg/mL) lead compounds because of their ability to kill larvae and use them as pesticides. All compounds (1a-1l) were found to be low toxic, whereas compounds 1b, 1d, and 1k were screened for antifeedant screening of non -aquatic target for the toxicity measurement against marine fish Oreochromis mossambicus at 100 µg/mL caused 0% mortality in within 24 h. Molecular docking studies of synthesised compound 1b and permethrin docked with 3OGN, compound 1b demonstrated a greater binding affinity (-9.6 kcal/mol) compared to permethrin (-10.5 kcal/mol). According to these results, the newly synthesised geranylacetone derivatives can serve as lead molecules of larvicides agents.